2021
DOI: 10.1097/fjc.0000000000001003
|View full text |Cite
|
Sign up to set email alerts
|

Açaí Reverses Adverse Cardiovascular Remodeling in Renovascular Hypertension: A Comparative Effect With Enalapril

Abstract: This study aimed to determine if açai seed extract (ASE) could reverse pre-existing cardiovascular and renal injury in an experimental model of renovascular hypertension (2 kidney, 1 clip, 2K1C). Young male rats (Wistar) were used to obtain 2K1C and sham groups. Animals received the vehicle, ASE (200 mg/kg/d), or enalapril (30 mg/kg/d) in drinking water from the third to sixth week after surgery. We evaluated systolic blood pressure by tail plethysmography, vascular reactivity in the rat isolated mesenteric ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
4
5
0
Order By: Relevance
“…However, nobiletin treatment alleviated LV abnormalities in 2K-1C hypertensive rats. This finding is consistent with a previous review showing that LV hypertrophy and fibrosis are commonly found in pathologic hearts, contributing to LV dysfunction 42 , 43 . Cardiac hypertrophy is mainly caused by an adaptive response to chronic high-pressure load to preserve cardiac output 44 .…”
Section: Discussionsupporting
confidence: 93%
“…However, nobiletin treatment alleviated LV abnormalities in 2K-1C hypertensive rats. This finding is consistent with a previous review showing that LV hypertrophy and fibrosis are commonly found in pathologic hearts, contributing to LV dysfunction 42 , 43 . Cardiac hypertrophy is mainly caused by an adaptive response to chronic high-pressure load to preserve cardiac output 44 .…”
Section: Discussionsupporting
confidence: 93%
“…After açai supplementation, myocardial infarction rats had a lower concentration of MDA, an oxidative stress marker, and cardiac remodeling [ 45 ]. Similar results were found with açai seed extract in the renovascular hypertension animal model and obese high-fat diet-fed mice, demonstrating a protective effect in cardiovascular diseases probably due to its antioxidant properties [ 43 , 44 ]. Orange juice ( Citrus sinensis ), grape seed extract, and jaboticaba ( Myrciaria jaboticaba ), fruits with antioxidant components, also attenuated cardiac remodeling after myocardial infarction in rats [ 46 , 47 , 48 ].…”
Section: Evidence Of Oxidative Stress As a Therapeutic Target Against...supporting
confidence: 75%
“…Indeed, studies with different diets and natural food rich in antioxidants have investigated its role in preventing and treating cardiovascular diseases [ 15 ]. Recently, three experimental studies evaluated the role of açai, a fruit rich in polyphenols, in different models of cardiovascular disease in rats [ 43 , 44 , 45 ]. After açai supplementation, myocardial infarction rats had a lower concentration of MDA, an oxidative stress marker, and cardiac remodeling [ 45 ].…”
Section: Evidence Of Oxidative Stress As a Therapeutic Target Against...mentioning
confidence: 99%
“…Thus, the authors concluded that açaí oil is antihypertriglyceridemic, anticholesterolemic, and advantageous in the treatment of dyslipidemia [ 107 ]. For this reason, açaí oil may also have potential as a preventive agent for CVDs [ 20 , 120 ].…”
Section: Biological and Pharmacological Effectsmentioning
confidence: 99%